Influence of the Dry Friction Suspension System Characteristics on the Stick-Slip of Vertical Vibration of a Three-Piece Bogie - Dali Lyu; Qichang Zhang; Kewei Lyu; Jiaxing Liu; Yulong Li (Shock and Vibration)
The dry friction structure is a commonly used vibration-damping method for railway vehicles. Insufficient vibration damping performance will cause excessive vibration of the vehicle, which is not conducive to the safety of the vehicle. However, the mechanism of vibration damping and the cause of clamping stagnation have not been well resolved. This paper uses the analytical method, numerical method, and finite element method to analyze the vertical dynamic characteristics of the simple suspension system with dry friction and demonstrates that the numerical method is an effective method to study the dry model. The conditions for the system to produce sticking events were analyzed by the numerical method. The analysis shows that the system's excitation is too small, which causes clamping stagnation to the system. The reduction of the wedge angle and the friction coefficient are conducive to eliminating sticking. A negative side frame angle is conducive to reducing the high-frequency energy of the excitation. Decreasing spring stiffness or increasing system mass to reduce system frequency can reduce sticking events. The mutual verification of different methods confirms the correctness of the analysis method and analyzes the cause of sticking or clamping stagnation from the mechanism, which provides a new idea for the design and improvement of the dry friction damping system of railway vehicle bogies.